Inclusive Food Systems: Before and After COVID-19 - Swinnen, Johan (2020)
GLOBAL FOOD POLICY REPORT IFPRI South Asia Discussion of the 2020 Global Food Policy Report Co-Organized by IFPRI, Indian Council of Agricultural Research Johan Swinnen (ICAR), and Trust for Advancement of Agricultural Sciences (TAAS) JUL 6, 2020 - 04:30 PM TO 06:00 PM IST